The lost child complex in Australian film jung, story and playing beneath the past - Waddell, Terrie (Routledge, 2019)
The Lost Child Complex in Australian Film is a unique and compelling work which will be highly relevant for academics and students of Jungian and post-Jungian ideas, cultural studies, screen and media studies. It will also appeal to Jungian psychotherapists and analytical psychologists as well as readers with a broader interest in Australian history and politics